Are we Building a Better World with ICTs? Empirically Examining this Question in the Domain of Public Health in India. Issue 1 (2nd January 2016) - Sahay, Sundeep
Abstract : As social scientists engaged in Information Technologies for Development (IT4D), a question we need to necessarily engage with is "are we building a better world with Information and Communication Technologies (ICTs)?" This question, first posed by Professor Geoff Walsham in the IS field, was the topic of my plenary discussion at the IFIP 9.4 meeting in Jamaica 2014, and had now been further developed to this "view from practice" paper for this journal. A first step in this paper has been the reformulation of the question which Professor Walsham raised: "What distortions and obstacles are created by the historical, material, and institutional conditions, and how these shape our efforts of ICTs creating a better world?" This reformulation is done to bring in more explicitly the political dimension into the question, and to nuance the technological deterministic argument implied in the question of technology (always) creating a better world. Taking an empirical example of an ICT intervention from the public health sector in India, deliberately chosen to emphasize distortions typically seen is similar Information and Communication Technologies for Development (ICT4D) projects, the analysis focuses on understanding the conditions of distortions, why they occur, and what can be done differently to contribute to our notion of a better world.